PERANCANGAN MEDIA PROMOSI BERBASIS WEB DENGAN METODE WATERFALL : WEB-BASED PROMOTIONAL MEDIA DESIGN WITH WATERFALL METHOD - Nofri Yudi Arifin (Engineering and Technology International Journal, 2020)
Website as a medium of providing complete information and easy access because it can be opened anywhere. The website will show a strong sense of navigational touch and ease of use of online displays, so it is a must for business people engaged in barbershop services to have their own website. A website will help potential customers get to know services or information about business actors. The UI (User Interface) website design at Rendi Barbershop displays interface design not only about colors and shapes, but also about presenting the right tools to achieve goals. such as displaying promotional information on the website to increase the number of customers who come.